ASSESSING THE DETERMINANTS OF BANK PROFITABILITY IN CHINA FROM 2012 TO 2019 - Li, Yu (2020)
This article aims to investigate the factors affecting the bank profitability of Chinese commercial banks over the period 2012-2019. To ensure that the research results are not affected by the financial crisis and the modernization reform and partial privatization of Chinese commercial banks, we select the sample data between 2012 and 2019. The sample data consist of 170 commercial banks in China, including 5 state-owned commercial banks, 12 joint-stock commercial banks, and 153 city commercial banks. The approach of the two-step generalized method of moments (GMM) is used in this paper. The profitability determinants used include bank-specific as well as macroeconomic variables. The results indicate that bank profitability is positive and significantly correlated with GDP growth, inflation, and Z-Score in China. Moreover, the empirical results reveal that the same independent variable has different effects on different dependent variables to measure bank profitability, such as operating efficiency, asset quality, and bank size. The author concludes that excess capital adequacy, high unemployment rate, and low operating efficiency are associated with low bank profitability. Furthermore, liquidity has no impact on Chinese commercial banks during the period. This paper offers some suggestions for promoting the profitability of Chinese commercial banks. Further research can be detailed in examining each commercial bank branch in China and include more variables. For instance, industry variables, taxation, exchange rate, and interest rate. In addition, a comparative analysis of the profitability of different types of commercial banks in China could be conducted in further research. Keywords: Bank profitability, Bank-specific, Macroeconomic, GMM, Return on average equity (ROAE), Net interest margin (NIM), China